The good news of the body : sexual theology and feminism - Isherwood, Lisa (Studies in theology and sexuality, 2000)
This book examines the power to define sexuality. It asks whether women are even present in the many acts of religious/sexual intercourse that define and control, but rarely engage them. A number of authors reflect from varying perspectives on the status of women within patriarchal understandings of sexuality. They take seriously the bodies of women as sites of resistance to patriarchy, in the pain of those bodies, their fecundity and their capacity for erotic revolution. For this book also explores ways to rebel!